Explore Adult Learning Motivations of Various Training Levels - Pierog, Anita (International Journal of Engineering and Management Sciences, 2017)
Continuous learning is part of everyday life. It may be formal, non-formal or informal nature. The formal learning that takes place at school, is the basis of expertise. Why someone sitting to school? There can be given many answers to this question. The motivation for learning develops due to both internal and external factors. And even age groups and training as equally different. With regard to adult learning motivation was examining several surveys. The study is a summary of the test results. There was three target group: high school seniors, correspondence master's students and participants accredited training. The surveys set out to discover Why learn the various forms of training. The questions in each test were different but comparable. For participants accredited training habitual motivation is crucial. Their joy and pride of the family is less important to them. , Correspondence master's students were considered the most important things income, learning, and knowledge. Although the perception of other age groups, both the habitual and the actual motivation appears in every group. While high school students based on the results we can say that the more motivation to achieve a goal, such as employment, income acquire. so prominent the habitual motivation. In their case it emphasized that a distinction was made between friendship and relationship network. Namely, the friendships are not identified with the mere knowledge that may be necessary in order to achieve future goals.